The Formation of a Marine Bonebed at the Upper Cretaceous Dinosaur Park - Bearpaw Transition of West - Central Saskatchewan, Canada - Street, Hallie P.; Bamforth, Emily L.; Gilbert, Meagan M. (Frontiers in Earth Science, 2019)
A marine bonebed from the Campanian (Upper Cretaceous) Bearpaw – Dinosaur Park Formation transition, containing both micro- and macrovertebrate fossils and trace fossils, was discovered in west-central Saskatchewan, Canada. The bonebed formed during transgression of the Western Interior Seaway, with the stratigraphy of the area displaying extensive interfingering of these terrestrial and marine facies. The macrovertebrate fossils occur in a layer of fine-grained, unconsolidated sand. Directly overlying this stratum is a layer of sulfur-rich, medium-grained sandstone, containing the microvertebrate fossils. Most of the material in both layers is highly encrusted in gypsum. The bonebed formed in a barrier island system over three stages: original deposition of marine reptile bones in a silled basin over a period of sediment starvation, redeposition and burial of the bone material due to higher energy flow through the basin, and deposition of bony and cartilaginous fish material during a period of water stratification and subsequent euxinic conditions. Because sediment deposition rates were low when the marine reptile bones accumulated, these elements spent extended periods at the sediment-water interface, allowing them to become bioeroded. The bioerosion at this site takes two main forms: parallel-sided boreholes about one cm wide, and extensive hollowing out of the cancellous bone. Although the invertebrate tracemakers were not preserved the boreholes resemble clavate borings made by bivalves, and the hollowing could have been caused by polychaete worms or grazing gastropods. The presence of sulfur-rich deposits and chemosymbiotic Chondrites isp. traces in the layer above the bonebed suggest the development of a stratified water column in the basin, with euxinic (anoxic and sulfuric) conditions near the seafloor. Disruption of the water column culminated in a mass die-off of non-air breathing vertebrates in the surface waters and constitutes the microvertebrate layer of the bonebed. Marine reptile bonebeds are rare in the fossil record, and this site represents the first time a vertebrate assemblage has been described from a barrier island system in Saskatchewan. This study will help further our understanding of the transition between the Dinosaur Park and Bearpaw formations, two of the best-known Campanian fossil-bearing deposits in Canada.